NUTRITIVE CHARACTERISTICS OF TWO TROPICAL AQUATIC WEEDS FOR RUMINANTS - ADERIBIGBE, A. O.; BROWN, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The nutritive values of water hyacinth (Eichhornia crassipes) and water lettuce (Pistia stratiotes) for ruminants were evaluated using chemical and mineral analyses, ensiling, in vitro and in situ digestion studies. The aquatic weeds contained lower levels of dry matter (DM), but higher levels of CF and ash than GG. WL contained higher levels of organic matter (0M), CP and crude fibber (CF) that W H. CP was concentrated in the leaves of the aquatic weds. The roots contained the highest amount of ash, while the stems contained the highest level of CF. WL contained higher levels of potassium, calcium, iron, magnesium and copper than WH and GG. Silage pH was lower for the WL silages than for the other silages and was also lower for urea than for other N sources. The Lowest pH was obtained when WL was supplemented with 20% maize using blood meal or urea as N sources. Silage fermentation was better for WH and WL than tar GG. The percent in vitro dry matter digestibility (IVDMD) was higher (P<0.05) for the WH and WL silages than for the GG silages with no difference (P>O.05) between the WH and WL silages. IVDMD for the various hays followed the trend WL>GG>WH(P>0.05). the percent in situ dry matter digestibility (ISDMD) for the various hays followed the trend WL>GG>WH(P>0.05).